2023
DOI: 10.1109/access.2023.3268174
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms to Measure Area and Volume on 3D Face Models for Facial Surgeries

Abstract: The increased availability and affordability of 3D scanning technology due to recent advancements have made pre and post-operative analysis for facial surgeries more convenient and accurate through the use of 3D patient scans. However, to perform a more comprehensive analysis using area and volume measurements, it is necessary to develop new software tools that include the appropriate algorithms. Without the right algorithms, any software tool cannot perform its intended tasks effectively. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Its potential within academic settings, extends to assisting in the generation of code for studying 3D facial models, as well as aiding in preparation for plastic surgery examinations. Few authors reported that correct code generation required human prompting various times 15 . Other than plastic surgery examination, ChatGPT's abilities have been previously tested against exams like USMLE 49 , in which it cleared the exam but did not score a high grade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its potential within academic settings, extends to assisting in the generation of code for studying 3D facial models, as well as aiding in preparation for plastic surgery examinations. Few authors reported that correct code generation required human prompting various times 15 . Other than plastic surgery examination, ChatGPT's abilities have been previously tested against exams like USMLE 49 , in which it cleared the exam but did not score a high grade.…”
Section: Discussionmentioning
confidence: 99%
“…Topsakal et al; demonstrated that ChatGPT is capable of generating code to compute the area and volume of regions on a 3D face model, using multiple prompts. 15 ChatGPT has understanding for oculoplastic research and can conduct thorough literature reviews, proposing novel experiments, improving surgical results through personalized surgical planning and patient communication within this domain. 16 Highlighting the implications of ChatGPT in plastic surgery research, Najafali et al 21 reported its ability to perform PRISMA systematic review and metanalyses from its own dataset.…”
Section: Characteristics Of Manuscriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently introduced area and volume measurement techniques for facial surgeries, aimed at augmenting surgeons' abilities to precisely analyze facial structures and plan surgeries. This novel addition to facial analysis is intended to significantly improve surgical outcomes and enhance the overall success of facial surgical procedures [12,13]. We have developed open-source algorithms to measure area and volume on a 3D facial model [13] and then utilized these algorithms to enhance the free web-based software called Face Analyzer [14] to help surgeons perform a more in-depth analysis of a patient's face [1].…”
Section: Introductionmentioning
confidence: 99%
“…This novel addition to facial analysis is intended to significantly improve surgical outcomes and enhance the overall success of facial surgical procedures [12,13]. We have developed open-source algorithms to measure area and volume on a 3D facial model [13] and then utilized these algorithms to enhance the free web-based software called Face Analyzer [14] to help surgeons perform a more in-depth analysis of a patient's face [1]. The Face Analyzer software, hosted at digitized-rhinoplasty.com, is now capable of measuring the area and volume of certain regions, such as the dorsal hump, nasal dorsum, root of the nose (Radix), and tip of the nose, and it is based on several previous works [10,12,13].…”
Section: Introductionmentioning
confidence: 99%